SF1-specific deletion of the energy sensor AMPKγ2 induces obesity - Óscar Freire-Agulleiro; Ánxela Estévez-Salguero; Vitor Ferreira; Cassie Lynn Holleman; Julia García-Currás; Ismael González-García; Rubén Nogueiras; Manuel Tena-Sempere; Cristina García-Cáceres; Carlos Diéguez; Miguel López (Molecular Metabolism)
Objective: AMP-activated protein kinase (AMPK) is a heterotrimer complex consisting of a catalytic α subunit (α1, α2) with a serine/threonine kinase domain, and two regulatory subunits, β (β1, β2) and γ (γ1, γ2, γ3), encoded by different genes. In the hypothalamus, AMPK plays a crucial role in regulating energy balance, including feeding, energy expenditure, peripheral glucose and lipid metabolism. However, most research on hypothalamic AMPK has concentrated on the catalytic subunits AMPKα1 and AMPKα2, with little focus on the regulatory subunits. Methods: To fill this gap of knowledge, we investigated the effects of selectively deleting the regulatory isoform AMPKγ2, which is a primary “energy sensor”, in steroidogenic factor 1 (SF1) neurons of the ventromedial hypothalamic nucleus (VMH). Complete metabolic phenotyping and molecular analyses in brown adipose tissue (BAT), white adipose tissue (WAT) and liver were carried out. Results: Our findings reveal that, in contrast to the obesity-protective effect of the genetic deletion of AMPKα subunits, the loss of AMPKγ2 in SF1 neurons leads to a sex-independent and feeding-independent obesity-prone phenotype due to decreased thermogenesis in brown adipose tissue (BAT) and reduced browning of WAT, resulting in lower energy expenditure. Additionally, SF1-Cre AMPKγ2 mice exhibit hepatic lipid accumulation, but surprisingly maintain normal glucose homeostasis. Conclusions: Overall, these results highlight the distinct roles of AMPK subunits within the hypothalamus.